General decay for a porous thermoelastic system with a memory. Issue 3 (17th February 2019) - Afilal, Mounir; Soufyane, Abdelaziz
ABSTRACT: In this paper, we consider a linear damped porous thermoelastic system of memory type where the heat conduction is given by Cattaneo's Law . We establish a general decay results using an appropriate Lyapunov functional.